Influence of Cultural Norms on Student Academic Performance in Marsabit Central Sub-County - Ojwang, Oscar; Asatsa, Stephen; Koros, Peter (African Journal of Education and Practice, 2024)
Purpose: The purpose of the study was to assess the influence of cultural norms on student academic performance in Marsabit Central Sub-County Methodology: The study adopted a mixed method research approach. A convergent parallel design was used. The study adopted a mixed sampling technique of both probability (stratified sampling) and non-probabilistic sampling (purposive sampling) techniques to determine the sample population and size for the study. The study obtained its study population from the six secondary schools in Marasabit Central sub-county hence the general sample was obtained purposively but in the presentation of their respondents was stratified arranged to give distinct categories of their correspondence. Data was collected using questionnaires, interview guides and document analysis guide. Validity and reliability were attained following an expert opinion by the study supervisors and were tested using the Cronbach alpha reliability test in determining the tools effectiveness in data collection. Quantitative data was used to analyze descriptive statistics while qualitative data was analyzed using content analysis technique. Findings: The study found out that cultural practices had an influence on learners’ academic performance. Unique Contribution to Theory, Practice and Policy: The study recommends schools to organize academic clinics, mentorship programmes, strengthen guidance and counseling and peer counseling in schools, and the government to address shortage of teachers, insecurity, government tuition subsidy remittance on time, provision of infrastructural facilities to enable learning, need for sensitization of the community on importance of school and alternate measures on when and how to go about their cultural traditional norms and avail basic resources like water in schools. These were the substratum influence affecting the learner’s performance.